Short Introduction of Contract Law in Vietnam (Lex Jurnalica, 2013)
AbstractContract law is a vital aspect of all jurisdictions. It covers all everyday activities of the social-economic society of all countries, including developed and developing ones. Developed countries, based on strong economic foundations, still perfect the contract law to meet the needs of new situations. For developing countries, if they want to integrate into the international economy, they must continuously improve their laws, and contract law is one of the most important norms. Vietnam, a developing country undergoing the integration, must follow the general regulation which is perfecting its contract law. This short article focuses on the brief history and introduces basic contents of Vietnamese contract lawKeywords: contract, law, Civil CodeÂ AbstrakHukum kontrak merupakan aspek penting dari semua yurisdiksi. Ini mencakup semua kegiatan sehari-hari masyarakat sosial-ekonomi dari semua negara, termasuk negara maju dan negara berkembang. Negara-negara maju, didasarkan pada fondasi ekonomi yang kuat, masih menyempurnakan hukum kontrak untuk memenuhi kebutuhan situasi baru. Untuk negara-negara berkembang, jika mereka ingin berintegrasi ke dalam ekonomi internasional, mereka harus terus meningkatkan hukum mereka, dan hukum kontrak adalah salah satu norma yang paling penting. Vietnam, negara berkembang mengalami integrasi, harus mengikuti ketentuan umum yang menyempurnakan hukum kontrak. Artikel singkat ini berfokus pada sejarah singkat dan memperkenalkan isi dasar hukum kontrak Vietnam.Kata kunci: kontrak, hukum, Hukum Perdata